Study and peculiarity of the epic "Hayrat ul-Abror" by Alisher Navoi - Nuriddinova, Nigora Sharipova (Indonesian Journal of Education Methods Development, 2019)
The article reviews about the study, peculiarities of the First Epic of Alisher Navoi "Khamsa""Hayrat ul-Abror", its distinctive features from other khamsanavis epic, as well as the problems waiting for its solution in the field of khamsashunoslik on the work.